SOME NOTES ON THE SUBSTANTIAL CHANGES OF SPATIAL PLANNING PROCESS IN WEST JAVA PROVINCE - Priastono, Eko (Jurnal Inspirasi, 2018)
Since the issue of the new Spatial Planning Law (Law number 26/2007) in Indonesia, the role and authority of provincial governments and of local governments (regency/municipality) in spatial planning is differentiated and stated explicitly. This paper is a reflection on the process spatial planning formulation according to the Law Number 26/2007 about Spatial Planning, using West Java Province experience in 2010 as a reference. By comparing the principles of Law 26/2007 will be elaborate with the actual experience of West Java in formulating the spatial plan, along with some notes on the obstacles and difficulties in the process will be notified. By doing so, it is expected that by reflecting on obstacles and hindrances, in the future the weaknesses of spatial planning implementation can be anticipated beforehand. Strong demand for the perfect spatial plan (regional as well as local) and expectation that the spatial plan should accommodate all human endeavors related with space, must be accompanied by appropriate supporting facilities. The inexistence of those supporting facilities may hindrance the implementation of the plan, and on the contrary, it may trap planning actors into problems which substantially outside the range of spatial planning.